A systematic review of the current evidence from randomised controlled trials on the impact of medication optimisation or pharmacological interventions on quantitative measures of cognitive function in geriatric patients - Pazan, Farhad; Burkhardt, Heinrich; Wehling, Martin (Drugs & aging, 2022)
Cognitive decline is common in older people. Numerous studies point to the detrimental impact of polypharmacy and inappropriate medication on older people’s cognitive function. Here we aim to systematically review evidence on the impact of medication optimisation and drug interventions on cognitive function in older adults.
Gesehen am 31.01.2023